Losers of the Falling Oil Prices: Changes in Oil Vulnerability in the Oil Exporting Countries - Nagy, Zoltán; Szep, Tekla Sebestyen (International Journal of Energy Economics and Policy, 2016)
The oil market was relatively balanced between 2011 and 2013 at around 100 USD. In the second half of 2014 the sharp decline in oil prices was an unexpected event for most of the market players. The size of price drops justifies an analysis of the oil vulnerability of the most significant net oil exporting countries. In this study many types of trade statistics (export intensity index, terms of trade index, export sensitivity, Herfindahl-Hirschman index), and furthermore the Bennett method are applied to quantify the oil vulnerability of the 14 most important oil exporting nations. It is possible to identify country groups, which enables us to differentiate the applicable economic instruments and make policy recommendations. Keywords: oil prices, vulnerability, energy security JEL Classifications: F19, Q41, Q43